2016
DOI: 10.14260/jemds/2016/865
|View full text |Cite
|
Sign up to set email alerts
|

CLINICOPATHOLOGICAL ANALYSIS OF OVARIAN TUMOURS IN A TERTIARY CARE INSTITUTE AND THE ROLE OF ER, PR AND HER-2/neu IN SURFACE EPITHELIAL TUMOURS OF OVARY

Abstract: BACKGROUNDOvarian tumours account for 6% of all cancers in women and is the 5th leading cause of death in women in India. Ovarian neoplasms are increasingly important not only because of the diverse entities, but more so because they have gradually increased the mortality due to female genital cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The incidence of mucinous carcinomas of the ovary was much lower in all the studies mentioned which constituted 14.28% of cases in the present study. Thangaraj Priya et al, 12 also showed that papillary serous cystadenocarcinomas were the most common type among all malignant serous epithelial tumours of ovary. This could be due to the fact that malignant serous epithelial tumours of ovary display tumour heterogeneity.…”
Section: Discussionmentioning
confidence: 96%
“…The incidence of mucinous carcinomas of the ovary was much lower in all the studies mentioned which constituted 14.28% of cases in the present study. Thangaraj Priya et al, 12 also showed that papillary serous cystadenocarcinomas were the most common type among all malignant serous epithelial tumours of ovary. This could be due to the fact that malignant serous epithelial tumours of ovary display tumour heterogeneity.…”
Section: Discussionmentioning
confidence: 96%